2013
DOI: 10.1063/1.4821517
|View full text |Cite
|
Sign up to set email alerts
|

Study on dielectric and piezoelectric properties of 0.7 Pb(Mg1/3Nb2/3)O3-0.3 PbTiO3 single crystal with nano-patterned composite electrode

Abstract: Effect of nano-patterned composite electrode and backswitching poling technique on dielectric and piezoelectric properties of 0.7 Pb(Mg 1/3 Nb 2/3 )O 3 -0.3 PbTiO 3 was studied in this paper. Composite electrode consists of Mn nano-patterns with pitch size of 200 nm, and a blanket layer of Ti/Au was fabricated using a nanolithography based lift-off process, heat treatment, and metal film sputtering. Composite electrode and backswitching poling resulted in 27% increase of d 33 and 25% increase of dielectric con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[ 60 ] The lead magnesium niobate and lead titanate (PMN‐PT) as the piezoelectric SC can have the piezoelectric constant ( d 33 ) up to 2000 pC N −1 which is four to six times higher than PZT piezoelectric ceramic. [ 61 ] Domain engineering by manipulating the domain structure through patterned electrodes [ 62 ] and poling methods [ 63 ] enhances the piezoelectric performance of relaxor‐PT SCs. This technique leads to have superior piezoelectric properties in SCs in compare with ferroelectric ceramics.…”
Section: Piezoelectric Effect and Piezoelectric Materialsmentioning
confidence: 99%
“…[ 60 ] The lead magnesium niobate and lead titanate (PMN‐PT) as the piezoelectric SC can have the piezoelectric constant ( d 33 ) up to 2000 pC N −1 which is four to six times higher than PZT piezoelectric ceramic. [ 61 ] Domain engineering by manipulating the domain structure through patterned electrodes [ 62 ] and poling methods [ 63 ] enhances the piezoelectric performance of relaxor‐PT SCs. This technique leads to have superior piezoelectric properties in SCs in compare with ferroelectric ceramics.…”
Section: Piezoelectric Effect and Piezoelectric Materialsmentioning
confidence: 99%
“…To the best of our knowledge, the periodic poling has not been demonstrated for nonlinear PDC in bulk PMN‐PT materials. However, a microscale periodically poled PMN‐PT with precise domain structure down to 5 µm has been demonstrated by electron beam patterning technique and also 200 nm pitch size by backswitch poling using nanopatterned composite electrodes . The main issues with PMN‐PT periodic poling has been the formations of cracks but very recently, there has been an important progress made in achieving high optical quality monodomain state in PMN‐PT by using prepoling thermal annealing to prevent cracking which is an important step for nonlinear optical applications of PMN‐PT material family.…”
Section: Introductionmentioning
confidence: 99%
“…10) Besides, domain wall engineering by patterned electrodes could lead to the increase of the piezoelectric properties of relaxor-PT crystals when decreasing domain sizes or increasing domain wall motion. [11][12][13][14] Recently, Yamamoto and Yamashita et al 15,16) revealed that alternate current (electric field) poling (ACP) for PMN-xPT SCs is a very cost-effective process of building an engineering domain, hence both dielectric and piezoelectric properties were enhanced compared to those of conventional direct current (electric field) poling (DCP). Furthermore, X-ray diffraction (XRD) results showed ACP may create new domain structures and phases, owing to the very different diffraction peaks between non-poling (NOP), DCP, and ACP.…”
Section: Introductionmentioning
confidence: 99%